Male throat colour polymorphism is related to differences in space use and in habitat selection in tree lizards. (20th June 2018) - Paterson, J. E.; Blouin‐Demers, G.
Abstract: Habitat selection is the disproportionate use of some habitats relative to their availability and is used by animals to maximize fitness. Habitat selection has been the dominant framework for predicting the spatial distribution of animals, but different habitat selection strategies can occur within a population when there are physical or behavioural differences between individuals. Colour polymorphism is often linked to differences in other behavioural and morphological traits, and may therefore affect habitat selection strategy. Male ornate tree lizards ( Urosaurus ornatus ) exhibit a throat colour polymorphism associated with differences in behaviour and in reproductive strategy. Blue‐throated males are dominant and defend home ranges containing several females; orange‐throated males are either nomadic or sedentary and do not defend territories; and yellow‐ or green‐throated males are reproductive parasites that sneak copulations with females. We tested the hypothesis that throat colour in tree lizards affects habitat selection and space use with mark‐recapture data collected from 10 sites in the Chiricahua Mountains of southeastern Arizona, USA. We found that males with green throats moved more than males with blue throats, and that males with orange throats occupied smaller home ranges. Male ornate tree lizards were closer to the highest quality habitat than if their spatial distribution was random, and green‐throated males had a more marked preference for the highest quality habitat than blue‐throated males. We found no difference in the departures of body temperatures from the preferred body temperature range between males of different throat colours. Survival rates were similar for blue‐, green‐ and orange‐throated males. We demonstrated that throat colour polymorphism in ornate tree lizards is related to habitat selection strategy and this may help maintain the colour polymorphism. Abstract : Colour polymorphism is common in animals, but is evolutionarily puzzling because phenotypes with a fitness advantage should become fixed in a population. We demonstrated that throat colour polymorphism in ornate tree lizards is related to habitat selection strategy and this may help maintain the colour polymorphism.